1988
DOI: 10.1016/0167-8760(88)90032-3
|View full text |Cite
|
Sign up to set email alerts
|

Event-related potentials in autistic and healthy children on an auditory choice reaction time task

Abstract: Event-related potentials (ERPs) were recorded from midline (Fz, Cz, Pz) and lateral sites (F3, F4, P3, P4) in autistic children (n = 7) and age-matched controls (n = 9) on an auditory choice reaction time task. Subjects were asked to press a button to an infrequent target (500 Hz, P = 0.14) and to ignore higher pitched infrequent (2000 Hz, P = 0.14) and frequent (1000 Hz) non-targets. Autistic subjects made twice as many errors of omission as controls and showed a higher criterion (beta) for targets. Maximum E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
2
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 45 publications
1
54
2
2
Order By: Relevance
“…Children with autism had significantly shorter latencies of the P1, N1, P2 and P3 components (Martineau et al 1984). In an ACRT task with high functioning children, Oades et al found a shorter N1 latency with normal performance in autism compared to age matched controls (Oades et al 1988(Oades et al , 1990. Finally, Ferri et al (2003), in a study comparing children with autism with age-matched controls, found similar shorter latency of N1 in a standard oddball paradigm, with normal reaction times and accuracies (Ferri et al 2003).…”
Section: Low-level Auditory Processingmentioning
confidence: 60%
See 2 more Smart Citations
“…Children with autism had significantly shorter latencies of the P1, N1, P2 and P3 components (Martineau et al 1984). In an ACRT task with high functioning children, Oades et al found a shorter N1 latency with normal performance in autism compared to age matched controls (Oades et al 1988(Oades et al , 1990. Finally, Ferri et al (2003), in a study comparing children with autism with age-matched controls, found similar shorter latency of N1 in a standard oddball paradigm, with normal reaction times and accuracies (Ferri et al 2003).…”
Section: Low-level Auditory Processingmentioning
confidence: 60%
“…Developmentally, the P300 appears in the third to fourth years of life. Its amplitude increases with low stimulus probability, and its latency increases with task difficulty (McCarthy and Donchin 1976;Oades et al 1988).…”
Section: Higher-level (Cognitive) Processing: P3b and Ncmentioning
confidence: 99%
See 1 more Smart Citation
“…They have smaller and later P300s than healthy children. Oades et al (1988) reported that the P300 elicited by targets in an auditory choice reaction time task was smaller in amplitude and more anterior in distribution in autistic children than in healthy controls. However, P3a to rare nontargets was not reduced.…”
Section: Autistic Disordermentioning
confidence: 99%
“…Age-related 24 changes in evoked components provide indirect measures of auditory system maturation and reflect changes that occur during 25 development. We use magnetoencephalography (MEG) to investigate maturational changes in cortical auditory systems in left (LH) and 26 right (RH) hemispheres in children with autism disorder (AD) and Controls. We recorded auditory evoked responses over left and right 27 temporal lobes in 17 Control and 15 AD children in the age range 8-16 years and measured M100 latency as a function of age, subject 28 group and hemisphere.…”
mentioning
confidence: 99%